Data set from the project of warming-enchanced priority effects - Vass, Mate (Uppsala University, 2020)
The recipient communities were comprised of three different lake inocula (Lötsjön, Erken, or Grytsjön) inoculated separately into “foreign” Baltic Sea incubation medium. The dispersal source constituted of the Baltic Sea community inoculated into cell-free incubation medium. Both the recipient (early-arriving lake bacteria) and the dispersal source (late-arriving Baltic Sea bacteria) communities were incubated at three different temperatures (15, 20 and 25°C). Coalescence (dispersal) events were applied at three rates by replacing 0%, 5% and 20% cells in the recipient communities with cells from the dispersal source. The recipient communities were always mixed with the corresponding dispersal source replicate at the respective temperature level.

The dataset was originally published in DiVA and moved to SND in 2024.

The recipient communities were comprised of three different lake inocula (Lötsjön, Erken, or Grytsjön) inoculated separately into “foreign” Baltic Sea incubation medium. The dispersal source constituted of the Baltic Sea community inoculated into cell-free incubation medium. Both the recipient (early-arriving lake bacteria) and the dispersal source (late-arriving Baltic Sea bacteria) communities were incubated at three different temperatures (15, 20 and 25°C). Coalescence (dispersal) events were applied at three rates by replacing 0%, 5% and 20% cells in the recipient communities with cells from the dispersal source. The recipient communities were always mixed with the corresponding dispersal source replicate at the respective temperature level.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data set from the project of warming-enchanced priority effects
Keywords: Biology with specialization in Limnology; Biologi med inriktning mot limnologi; Ecology; Ekologi